Quantitative insights into the spatio‐temporal variation of Atlantic salmon ( Salmo salar ) biomass in a river catchment using eDNA metabarcoding - William Bernard Perry; Nigel Milner; Ifan Bryn Jâms; Mark de Bruyn; Steve J. Ormerod; Kristy Deiner; Holly M. Bik; Gary Carvalho; John Colbourne; Bernard Jack Cosby; Isabelle Durance; Simon Creer (Journal of Fish Biology, 2025)
Effective species conservation and management requires comprehensive biomonitoring, enhanced by combining traditional and newer methodologies, such as environmental DNA (eDNA) analyses. A seasonal pulse of spawning adult Atlantic salmon ( Salmo salar ) was detected by normalised eDNA 12S reads from metabarcoding, which facilitated estimation of spatial patterns in salmon biomass. A strong relationship was found between normalised reads in the lower section of the River Conwy (Wales, UK) and whole‐river adult biomass (estimated from rod catch data and a fish counter), explaining 61% of the variation in a linear regression. Moreover, the positive linear relationship between adult biomass and partial effect on normalised reads occurred after the biomass estimate exceeded 1500 kg, indicating a threshold where normalised reads become representative of biomass. The relationship observed between normalised reads and biomass, as well as the unique profiles of normalised reads at each of the sites, supports the hypothesis of limited eDNA transport among sampling sites that were 2–4 km apart. River pH showed a significant non‐linear relationship with normalised reads, with a peak in partial effect on normalised reads at pH 6.5. Partial effect on normalised reads also showed a positive linear relationship with flow (discharge), while also peaking at the highest average monthly air temperatures (14°C). These trends are contrary to what would be expected from eDNA decay, dilution or transport, demonstrating that metabarcoding is robust to such influences, reinforcing the interpretation of trends driven by Atlantic salmon ecology and physiology. For example, pH effects reflect beneficial conditions for eggs and perhaps habitat preference for spawners, flow effects reflect the annual return of salmon during higher flows which aid upstream migration, tributary entry and spawning, and, finally, temperature effects reflect higher metabolic rates and greater shedding of eDNA.

Using swim‐up traps to assess Arctic charr ( Salvelinus alpinus ) spawning habitat and the phenology and density of emergent fry - Antony Smith; Nigel Milner; Alexander Papadopoulos; Mathew Seymour; Gary Carvahlo (Fisheries Management and Ecology, 2024)
The Arctic charr ( Salvelinus alpinus ) is a species of cultural, economic and conservation importance, but hitherto, investigations of critical early life stages have been few. Here, at a lake in the United Kingdom, we used swim‐up traps to investigate the phenology of fry emergence and associations between fry density and habitat. The first emergence occurred on 4 or 5 March 2020 and 2021, with numbers peaking and remaining stable in the following 2 weeks. Emergence in 2021 had finished by 27 March but on the same date in 2020 emergence was ongoing when COVID‐19 ended sampling. Substrate particle size ranged 31–94 mm and was negatively correlated with fry density. Likewise, density was negatively correlated with water depth and aquatic plant cover, but there was no relationship with flow velocity. Traps were effective and non‐destructive for assessing the location and productivity of spawning sites for this locally threatened species.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

ECOLOGY OF SALMONIDS IN ESTUARIES AROUND THE WORLD - Nigel Milner (Journal of Fish Biology, 2017)

FISH ATLAS OF THE CELTIC SEA, NORTH SEA, AND BALTIC SEA - Nigel Milner (Journal of Fish Biology, 2016)

Fish scale δ15N and δ13C values provide biogeochemical tags of fish comparable in performance to element concentrations in scales and otoliths - Alice L. Ramsay; Nigel J. Milner; Roger N. Hughes; Ian D. McCarthy (Hydrobiologia, 2012)

Park Gazettement and Integrated Conservation and Development as Factors in Community Conflict at Bwindi Impenetrable Forest, Uganda - JULIA BAKER; E. J. MILNER‐GULLAND; NIGEL LEADER‐WILLIAMS (Conservation Biology, 2012)
Conflicts between protected‐area managers and local people are common, but the drivers of conflict are rarely analyzed. This limits opportunities to identify strategies that reduce conflict and the magnitude of resulting threats to conservation. Integrated conservation and development (ICD) was adopted at Bwindi Impenetrable Forest, Uganda, to reduce conflict during gazettement of the national park, but the success of this approach remains contested. We retrieved documents of conflict written by park staff and local people from 1986 through 2000 (before, during, and after gazettement). We extracted data on 48 incidences of violent conflict and categorized them by gazettement period, area, instigator, and type to undertake a historical analysis of the triggers of violent conflict at Bwindi. Before and during gazettement, local villagers instigated most of the conflict incidents when law‐enforcement efforts sought to halt commercial activities within Bwindi. No conflict arose from the arrest of villagers collecting subsistence resources during these periods. After gazettement, prohibitions on commercial activities continued to drive conflict even though villagers collecting subsistence resources were arrested more frequently than before gazettement, and local attitudes toward the park had improved following receipt of ICD benefits. Law‐enforcement efforts targeted commercial activities to reduce this threat to Bwindi's mountain gorillas ( Gorilla beringei beringei ), although the activities remained important income sources for people in villages near Bwindi. Losing commercial income following gazettement therefore appeared to be their primary motivation for instigating conflict with park rangers. Prohibitions on subsistence resource use triggered conflict less often. Our use of typologies for a multivariate conflict analysis demonstrates that by identifying differences between effects of conservation as drivers of conflict, conflict analysis can enable a more strategic deployment of conflict–resolution measures that could further conservation efforts. At Bwindi targeting ICD toward individuals who lost benefits from commercial activities may strengthen the role of ICD in conflict resolution and conservation.

Quantification of Extinction Risk: IUCN's System for Classifying Threatened Species - GEORGINA M. MACE; NIGEL J. COLLAR; KEVIN J. GASTON; CRAIG HILTON‐TAYLOR; H. RESIT AKÇAKAYA; NIGEL LEADER‐WILLIAMS; E.J. MILNER‐GULLAND; SIMON N. STUART (Conservation Biology, 2008)
The International Union for Conservation of Nature (IUCN) Red List of Threatened Species was increasingly used during the 1980s to assess the conservation status of species for policy and planning purposes. This use stimulated the development of a new set of quantitative criteria for listing species in the categories of threat: critically endangered, endangered, and vulnerable. These criteria, which were intended to be applicable to all species except microorganisms, were part of a broader system for classifying threatened species and were fully implemented by IUCN in 2000. The system and the criteria have been widely used by conservation practitioners and scientists and now underpin one indicator being used to assess the Convention on Biological Diversity 2010 biodiversity target. We describe the process and the technical background to the IUCN Red List system. The criteria refer to fundamental biological processes underlying population decline and extinction. But given major differences between species, the threatening processes affecting them, and the paucity of knowledge relating to most species, the IUCN system had to be both broad and flexible to be applicable to the majority of described species. The system was designed to measure the symptoms of extinction risk, and uses 5 independent criteria relating to aspects of population loss and decline of range size. A species is assigned to a threat category if it meets the quantitative threshold for at least one criterion. The criteria and the accompanying rules and guidelines used by IUCN are intended to increase the consistency, transparency, and validity of its categorization system, but it necessitates some compromises that affect the applicability of the system and the species lists that result. In particular, choices were made over the assessment of uncertainty, poorly known species, depleted species, population decline, restricted ranges, and rarity; all of these affect the way red lists should be viewed and used. Processes related to priority setting and the development of national red lists need to take account of some assumptions in the formulation of the criteria.